Suppressed Sr segregation and performance of directly assembled La0.6Sr0.4Co0.2Fe0.8O3-δ oxygen electrode on Y2O3-ZrO2 electrolyte of solid oxide electrolysis cells - Ai, N.; He, S.; Li, N.; Zhang, Qi; Rickard, William; Chen, K.; Zhang, T.; Jiang, San Ping (Elsevier SA, 2018)
Active and stable oxygen electrode is probably the most important in the development of solid oxide electrolysis cells (SOECs) technologies. Herein, we report the successful development of mixed ionic and electronic conducting (MIEC) La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF) perovskite oxides directly assembled on barrier-layer-free yttria-stabilized zirconia (YSZ) electrolyte as highly active and stable oxygen electrodes of SOECs. Electrolysis polarization effectively induces the formation of electrode/electrolyte interface, similar to that observed under solid oxide fuel cell (SOFC) operation conditions. However, in contrast to the significant performance decay under SOFC operation conditions, the cell with directly assembled LSCF oxygen electrodes shows excellent stability, tested for 300 h at 0.5 A cm−2 and 750 °C under SOEC operation conditions. Detailed microstructure and phase analysis reveal that Sr segregation is inevitable for LSCF electrode, but anodic polarization substantially suppresses Sr segregation and migration to the electrode/electrolyte interface, leading to the formation of stable and efficient electrode/electrolyte interface for water and CO2 electrolysis under SOECs operation conditions. The present study demonstrates the feasibility of using directly assembled MIEC cobaltite based oxygen electrodes on barrier-layer-free YSZ electrolyte of SOECs.